(untitled) (PerCursos, 2023)
The advent of the 1988 Federal Constitution and subsequent regulation of articles 182 and 183 significantly impacted Brazilian urban planning, introducing democratic urban management as the prerogative of municipalities. Focusing on popular participation in urban and regional planning processes, this study presents a qualitative approach and employs systematic review techniques to select the academic production of theses published between 2001 and 2022, in the National Base of Theses and Dissertations (BNDT). The main objective is to analyze the main conflicts and opportunities found through popular participation in democratic urban planning processes, with an emphasis on the Master Plan. Based on the descriptors “urban planning or master plan” and “social participation or democracy”, 21 theses were selected from the 64 found, as they gave prominence to the theme and presented empirical cases. The result is the diagnosis of the main challenges and opportunities found in different cities in the democratic processes of urban planning. It is possible to see that the obstacles are repeated and indicate a technical and centralizing pattern of the public entity, conflicts of interests between the different actors (state, municipal councils, businesspeople, popular movements, society), lack of knowledge of local dynamics and resistance to popular participation (hampered by lack of technical knowledge, opaque information and scarce opportunities). On the other hand, municipalities more prone to systemic openness signaled that experience based on learning, sharing of power and information are important points for achieving popular participation.